2007
DOI: 10.1586/17434440.4.6.781
|View full text |Cite
|
Sign up to set email alerts
|

BioSTAR®bioabsorbable septal repair implant

Abstract: Thousands of patients have had congenital defects of their intra-atrial septa successfully closed via percutaneous techniques in the cardiac catheterization laboratory for hemodynamic correction, stroke, migraine and decompression illness. However, currently available closure technologies leave a permanent cardiac implant in a relatively young patient population. As the first device incorporating a bioabsorbable material for the treatment of structural heart disease, BioSTAR is uniquely designed to remodel int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 101 publications
0
4
0
1
Order By: Relevance
“…The Bio-STAR implant has been available in Europe for patent oval foramen and atrial septal defect closure since 2006, and used in North America primarily for patent oval foramen closure for recurrent stroke prevention [22][23][24]. There is a limited pediatric experience and few studies assessing efficacy in secundum atrial septal defect closure [25].…”
Section: Discussionmentioning
confidence: 99%
“…The Bio-STAR implant has been available in Europe for patent oval foramen and atrial septal defect closure since 2006, and used in North America primarily for patent oval foramen closure for recurrent stroke prevention [22][23][24]. There is a limited pediatric experience and few studies assessing efficacy in secundum atrial septal defect closure [25].…”
Section: Discussionmentioning
confidence: 99%
“…No evidence of systemic inflammatory response was reported. Based on these encouraging short-term results, the BioSTAR device has been commercially approved in Europe for ASD and PFO closure in 2007 [ 72 , 73 , 74 , 75 ], and was used primarily for PFO closure for prevention of recurrent stroke in Canada [ 70 , 76 , 77 ]. Although the BioSTAR device was withdrawn from the market in 2011 because of late complications such as wire fractures and local inflammatory reactions [ 73 ], it represented an important breakthrough from non-bioabsorbable metal devices to bioabsorbable devices.…”
Section: Partially Biodegradable Devicesmentioning
confidence: 99%
“…Table 1 (Ref. [ 66 , 67 , 70 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 81 , 82 , 83 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 104 ]) depicts a variety of partially or fully biodegradable ASD/PFO occluders reported in the literature. Although most of the biodegradable devices showed promising short-term efficacy and safety in animal studies or in clinical trials, previous studies demonstrated that one of the drawbacks of biodegradable occluders was the suboptimal closure effect due to the occurrence of residual shunts after the degradation process initiates [ 73 , 74 ].…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Hence, biodegradable occluders have become a desirable alternative requirement. As early as 2003, the first partially degradable occluder, BioSTAR (NMT Medical, Boston, MA, USA) with a metallic permanent framework (MP35N) and a bioresorbable membrane made from intestinal collagen, was introduced [29][30][31][32][33]. A tremendous step forward from non-degradable metal occluders to biodegradable occluders was made based on the successful development of BioSTAR and desirable clinical results, even though it was withdrawn from the market due to complications with wire fractures and inflammatory reactions locally related to the biologic material of the membrane [33].…”
Section: Biodegradable Devicesmentioning
confidence: 99%